Monitoring of foodborne pathogens in some ready-to-eat fruits and vegetables in Shanghai in 2021 - QIN Xiaojie; LI Jiaming; SUN Tianmei; LIU Yangtai; WANG Xiang; LI Zhuosi; YANG Shuo; DONG Qingli (Shanghai yufang yixue, 2023)
ObjectiveThe contamination of foodborne pathogens in ready-to-eat fruits and vegetables in Shanghai was analyzed to provide a scientific basis for food safety， risk assessment and related supervision.MethodsFrom June to September 2021， a total of 143 batches of 12 kinds of ready-to-eat fruits and vegetables such as lettuce， chicory， and cherry tomatoes were collected from farmers’ markets， supermarkets， and e-commerce platforms. The total number of bacterial colonies， Salmonella， Listeria monocytogenes， Staphylococcus aureus， Cronobacter spp. and Shiga toxin-producing Escherichia coli in the samples were tested according to National Food Contamination and Harmfulness Risk Monitoring Manual.ResultsAmong the 143 batches， foodborne pathogens were detected in 68 batches， with a total detection rate of 47.55% （68/143）. A total of 79 strains of foodborne pathogens were detected. The detection rate of Staphylococcus aureus was the highest （32.87%， 47/143）， followed by Cronobacter spp. （20.98%， 30/143）， Salmonella （0.70%， 1/143）， Listeria monocytogenes （0.70%， 1/143）， Shiga toxin-producing Escherichia coli （0.00%）. Furthermore， the detection rate was higher in different ready-to-eat fruits and vegetables： chicory （17.33%）， cucumber （17.14%）， cherry tomatoes （16.00%）， and honeydew melon （15.38%）， respectively. Meanwhile， the contamination rate of pathogens in ready-to-eat fruits and vegetables from farmers’ markets， supermarkets， and e-commerce platforms was relatively high.ConclusionReady-to-eat fruits and vegetables in Shanghai are contaminated by foodborne pathogens. The prevention and control of the contamination of post-harvest fruits and vegetables should be strengthened to reduce the risk of foodborne disease outbreaks.